The Spinel LiCoMnO4: 5V Cathode and Conversion Anode. (October 2018) - Reeves-McLaren, Nik; Hong, Ma; Alqurashi, Hazzaa; Xue, Lu; Sharp, Joanne; Rennie, Anthony J.; Boston, Rebecca
Abstract: LiCoMnO4 was made at 550 °C in 2 h using a novel biotemplating synthetic methodology. High temperature heat treatment under flowing N2 was then used to prepare the cation-disordered rock salt, LiCoMnO3 . We demonstrate for the first time that both phases can operate as conversion anodes in lithium-ion batteries, operating at 0.7 V with specific capacities of 400 mAh g -1 . We also demonstrate that 1, 3-propane sultone can be used as an electrolytic additive to provide a modest boost to specific capacity in cells cycled at high potentials with LiCoMnO4 as the cathode.